THE INFLUENCE OF HALAL SLAUGHTER AND PRICE LEVEL ON PURCHASING DECISIONS AT CHICKEN SLAUGHTERHOUSES IN BANDA ACEH CITY - Jainul Ubaidillah; Chairul Fahmi; Muhammad Zulhilmi; Yusra Jamali (An Nuqud Journal of Islamic Economics, 2025)
Aceh, as an area that implements Islamic law, has people who are very concerned about the halalness of products, including chicken meat. However, there are still chicken slaughterhouses in Banda Aceh that are not halal certified. Despite this, many consumers continue to buy without questioning the slaughter process. Price fluctuations due to weather and seasonal demand also affect purchasing preferences. This study aims to analyze the effect of halal slaughter and price level on consumer purchasing decisions at chicken slaughterhouses in Banda Aceh City. A quantitative approach was used with data collection techniques through questionnaires to 100 respondents. Data analysis was carried out using multiple linear regression. The results showed that both halal slaughter and price level partially had a positive and significant effect on purchasing decisions. Simultaneously, these two variables also have a positive and significant effect. This finding indicates that the halal aspect of slaughtering as well as the price offered are the main factors in consumers' decision to buy chicken meat. Therefore, it is important for chicken slaughterhouse businesses to pay attention to these two aspects to increase consumer trust and loyalty.